Impact of Destination Attributes on Tourists Destination Selection: With Special Reference to Cultural Triangle of Sri Lanka - Mohamed A. M. Raazim; Munasinghege A. T. K. Munasinghe (Centre For Tourism Planning and Development, 2021)
Sri Lanka is one of the fastest-growing tourist destinations in the world. Amongst tourists’attractions, “Cultural Triangle”, a region of the cultural heritage of the country has becomethe highest income generating destination. However, when compared with the othertourists’ destinations of the country, the number of tourists visiting the cultural triangle islow. As the literature reveals, the attributes of the destination matter in destinationselection by the international tourists. Thus, considering the importance of this region asthe top income contributor but not in terms of the number of tourists' visits, this studyproblematizes the impacts of destination attributes on tourist`s destination selection.Accordingly, the objective of this study is to identify the destination attributes and theirrelationship with the tourists’ destination selection decisions. Data was collected throughquestionnaires from a sample of 222 foreign tourists who visited the cultural triangleduring 2019 through a selected travel agent. Results of the multiple regression analysisrevealed that attributes of Amenities, Destination Attractions, Accessibility, AncillaryServices, and Destination Environment as having a moderate positive relationship whilst,the service quality weak positive relationship with Tourist’s Destination selection.Destination attraction was identified as the most influential factor of all attributes. Thefindings of this study can be used by policymakers in developing destinations for tourists’attractions in the country.